Sintesis Dan Karakterisasi Karbon Aktif Terdoping Nitrogen Dari Limbah Kulit Kopi Arabika Bali Melalui Aktivasi Kimia Untuk Aplikasi Elektroda Superkapasitor - Muhammad Samsudin; Ilham Muzammir; Fandi Pradana (Lembaga Publikasi Ilmiah Nusantara, 2026)
Spent This study aimed to synthesize and characterize nitrogen-doped activated carbon derived from Bali. Arabica coffee husk waste through chemical activation and to evaluate its potential as a supercapacitor electrode material. Coffee husk waste was initially carbonized under a nitrogen atmosphere and subsequently activated using potassium hydroxide (KOH) to develop a porous structure and enhance the specific surface area. Nitrogen doping was then carried out using a nitrogen-rich precursor through thermal treatment at elevated temperatures. Material characterization was performed using Scanning Electron Microscopy (SEM), Brunauer–Emmett–Teller (BET) surface area analysis, Fourier Transform Infrared Spectroscopy (FTIR), and elemental composition analysis to investigate the morphology, pore structure, and surface functional groups of the carbon material. The results demonstrated that chemical activation successfully produced a hierarchical porous structure consisting of micropores and mesopores with a high specific surface area. SEM observations revealed a well-developed porous network, while FTIR and elemental analyses confirmed the successful incorporation of nitrogen atoms into the carbon matrix. The presence of nitrogen contributed to enhanced electrical conductivity, the formation of additional active sites, and improved electrode–electrolyte interactions. Electrochemical evaluation using cyclic voltammetry (CV) exhibited predominantly capacitive behavior with a notable pseudocapacitive contribution originating from nitrogen-containing functional groups. The nitrogen-doped activated carbon exhibited higher specific capacitance, excellent cycling stability, and high coulombic efficiency compared with the undoped carbon material. These findings demonstrate that the combination of chemical activation and nitrogen doping effectively improves the structural characteristics and electrochemical performance of activated carbon. The utilization of Bali Arabica coffee husk waste as a carbon precursor offers a sustainable, environmentally friendly, and value-added approach for developing high-performance electrode materials for modern energy storage applications.